Shores, surfaces and depths
1 online resource (xi, 252 pages)
Keywords: "This book examines the oceanic presence in life on Earth, and the ways that we engage with the oceanic worlds for play, pleasure, adventure and the pursuit of leisure and escape through tourism and travel. The oceanic 'turn' across the social sciences and humanities has produced a still proliferating opus of work that seeks to discover and emphasize oceanic presence in life on Earth. This literal and figurative 'unearthing' of blue spaces has encouraged scholars to gaze beyond the lands that have supported much of our experience and knowledge towards the gathering up of a more holistic appreciation of blue planetary life. This widening of scholarly attention -- from 'land' to 'sea' -- is occurring simultaneously across a range of disciplines and fields, including history, archaeology, anthropology, comparative literature, public policy, cultural studies, and geography. With an explicit focus on "leisure" and "tourism", this edited collection follows a growing appreciation that it is our seemingly inconsequential encounters - at play, for pleasure and on holidays - that are increasingly present and influential in our oceanic relations This volume will be of value to scholars and students interested in Social and Cultural history and environmental history and humanities"--